Judicial Restraint in Investment Treaty Arbitration: Restraint Based on Relative Suitability. (17th January 2014) - Van Harten, Gus
Abstract: This article examines how investment treaty arbitrators characterized their role in relation to other adjudicative forums. The discussion seeks to address situations in which the arbitrators' role overlapped with that of another adjudicative body because the claimant submitted, or could have submitted, its complaint against the state to domestic courts, a contractually agreed forum, or another international adjudicator. With a modest exception in the case of domestic courts, it was found overall that arbitrators constituted themselves as autonomous decision-makers and rarely referred to terms used by courts to restrain their role and manage overlaps with other adjudicators. Remarkably, had investment treaty tribunals taken a general position of restraint due to the role of other adjudicative forums—especially contractually agreed forums—then investor claims in many and perhaps most cases would have been stayed, at least, until a resolution in another forum. Much of the financial and other resources expended in investment treaty arbitration, and much of the compensation awarded against states, thus appears to have followed from the arbitrators' decisions about restraint.